Students' Dialogue Journal Writing: An Exceptional Communication Tool Between Teachers and Students - Amparo Clavijo Olarte (Asociación Colombiana de Profesores de Ingles, 2016)
The purpose of this paper is to present dialogue journal writing as an important part of ESL/EFL language instruction. Journal writing consists of students' daily writings where they freely express their feelings, worries and/or interests, and receive a response from the teacher.